2013
DOI: 10.1159/000354873
|View full text |Cite
|
Sign up to set email alerts
|

The Association Study of Plasma Levels of Pigment Epithelium-Derived Factor with Acute Coronary Syndrome in the Chinese Han Population

Abstract: Objects: To investigate the relationship between plasma levels of pigment epithelium-derived factor (PEDF) and acute coronary syndrome (ACS) in the Chinese Han population. Methods: Plasma PEDF levels were measured in 200 consecutive ACS patients and 160 age- and sex-matched healthy control subjects. Logistic regression analysis was performed to determine whether PEDF was an independently protective factor against ACS. All ACS patients were followed up for 6 months and the short-term major adverse cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…PEDF, a 50-kDa glycoprotein, has anti-inflammatory, antioxidant, antiangiogenic, antithrombotic, antitumorigenic, and neuroprotective properties [82] and is widely expressed throughout the human body. In ACS patients, plasma PEDF concentrations were significantly lower than the control group and associated with adverse cardiac outcomes after ACS [83]. PEDF can block platelet activation and aggregation [84] through its anti-inflammatory and antioxidative properties, leading to the inhibition of the vascular inflammation and the formation of a thrombus [85].…”
Section: Discussionmentioning
confidence: 99%
“…PEDF, a 50-kDa glycoprotein, has anti-inflammatory, antioxidant, antiangiogenic, antithrombotic, antitumorigenic, and neuroprotective properties [82] and is widely expressed throughout the human body. In ACS patients, plasma PEDF concentrations were significantly lower than the control group and associated with adverse cardiac outcomes after ACS [83]. PEDF can block platelet activation and aggregation [84] through its anti-inflammatory and antioxidative properties, leading to the inhibition of the vascular inflammation and the formation of a thrombus [85].…”
Section: Discussionmentioning
confidence: 99%
“…ACS patients, however, had decreased plasma and intraplatelet level of PEDF [ 16 ]. Meanwhile, we have previously shown that ACS patients had notably lower plasma PEDF level relative to the control group and lower PEDF level was further related to adverse cardiac outcomes after ACS [ 19 ], and that PEDF level remarkably decreased in CAD patients compared to the controls [ 20 ]. Therefore, it is not yet clear whether high or low PEDF serum level accelerates the development of these diseases.…”
Section: Overview Of Pedfmentioning
confidence: 99%
“…Additionally, our group has carried out recent studies on PEDF, ranging from clinical issues to molecular mechanisms. Initially, we found that plasma PEDF level was significantly lower in ACS patients, and lower PEDF level was associated with adverse cardiac outcomes after ACS [ 19 ]. Furthermore, our data showed that plasma PEDF level was significantly lower in CAD patients and PEDF may be used as a potential predicator for coronary severity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to cross-sectional design of these studies there are questions of whether elevation of PEDF was a cause or consequence of impaired vascular function, inflammation and atherosclerosis and whether PEDF levels are not elevated as a compensatory countersystem to attenuate the inflammation and atherosclerosis. Liu et al (2014) reported that plasma levels of PEDF were decreased in patients with acute coronary syndrome relative to control subjects, and lower PEDF values could predict future adverse CV events in these patients.…”
Section: Discussionmentioning
confidence: 98%